Pengembangan Media Pembelajaran Berbasis Articulate Storyline 3 Menggunakan Model Problem-Based Learning di Kelas IV Sekolah Dasar - Putra, Dimas Febrian; Zainil, Melva (Universitas Negeri Padang, 2024)
Development research was carried out against the background of the unavailability of learning media for flat and wide roving material by utilizing the Storyline 3 articulate application which can help students understand the concept of perimeter and flat area effectively. The research aims to create reliable and useful media based on the ADDIE approach carried out in grade IV SDN 12 Bukit Cangang and SDN 01 Benteng Pasar Atas. Data collection was carried out through validity sheets and response questionnaire sheets consisting of teacher and student responses using Likert scales. The learning media developed obtained validity test results with very valid categories and practical test results with very practical categories. As a result, the Articulate Storyline 3 application-based learning media developed has been considered feasible and valid for educational purposes. Students are very enthusiastic about using digital learning media because they are curious and enjoy playing with learning media. Problem-based learning has an impact on students because they become active and self-directed in solving problems immediately. So it becomes a unique experience for students.